Perforation of Meckel's diverticulum by a swallowed fish bone: case report and literature review - Santos, Bruno (J Surg Case Rep, 2019)
Meckel's diverticulum is the commonest congenital abnormality of the gastrointestinal tract. Most cases are asymptomatic and only incidentally found. Its perforation by a foreign body is an extremely rare event. A 53-year-old female presented to Emergency Department with abdominal pain on the right iliac fossa and vomiting. CT scan was performed and showed an intestinal perforation by a foreign body. Diagnostic laparoscopy identified a perforation of a Meckel's diverticulum by a fish bone and a laparoscopic stapled diverticulectomy was performed. Meckel's diverticulum complications are more common in childhood, usually as bleeding. In adults, intestinal obstruction and inflammation are the usual manifestations. Although most swallowed foreign bodies are harmless, in a small number of cases perforation may occur. Preoperative diagnosis of complicated Meckel´s diverticulum is challenging and can often mimic other more common conditions. Laparoscopy is a valuable tool for the diagnosis and treatment of complicated Meckel’s diverticulum.